2019
DOI: 10.1007/s11192-019-03089-w
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the analysis and evaluation of the research output of countries and institutions

Abstract: A plethora of bibliometric indicators is available nowadays to gauge research performance. The spectrum of bibliometric based measures is very broad, from purely size-dependent indicators (e.g. raw counts of scientific contributions and/or citations) up to size-independent measures (e.g. citations per paper, publications or citations per researcher), through a number of indicators that effectively combine quantitative and qualitative features (e.g. the h-index). In this paper we present a straightforward proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Despite these problems, the mean citation rate combined with the percentage of papers that reach the top citation rate—the HQSI —still seems to be a sufficiently adequate measure of what can be called the scientific wealth of nations, better than the mean citation rate alone (cf. Docampo & Bessoule, 2019; Harzing & Giroud, 2014; Horta, 2018; King, 2004; May, 1997; Rousseau & Rousseau, 1998). Even though it has been argued that the traditional method of counting citations may not be the most accurate or optimal measure of scientific excellence (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these problems, the mean citation rate combined with the percentage of papers that reach the top citation rate—the HQSI —still seems to be a sufficiently adequate measure of what can be called the scientific wealth of nations, better than the mean citation rate alone (cf. Docampo & Bessoule, 2019; Harzing & Giroud, 2014; Horta, 2018; King, 2004; May, 1997; Rousseau & Rousseau, 1998). Even though it has been argued that the traditional method of counting citations may not be the most accurate or optimal measure of scientific excellence (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Just as gross domestic product (GDP) is a measure of economic wealth, the mean citation rate per scientific article could be used as a measure of the scientific wealth of nations (King, 2004;May, 1997). The link between economic and scientific wealth has been repeatedly demonstrated (Cimini et al, 2014;Cole & Phelan, 1999;Docampo & Bessoule, 2019;Gantman, 2012;Hatemi-J et al, 2016;King, 2004;Kumar et al, 2016;May, 1997;Mueller, 2016;Prathap, 2017;Rousseau & Rousseau, 1998;Vinkler, 2008Vinkler, , 2018, meaning that the richer the country, the more money is invested into research and development (R&D) activities, which, in return, is expected to increase the quality of scientific publications. Yet, the relationship between economic and scientific wealth is not as simple and straightforward as is often presented.…”
mentioning
confidence: 99%
“…Many studies have demonstrated that scientific wealth depends on economic wealth (Allik et al, 2020;Cimini et al, 2014;Cole & Phelan, 1999;de Moya-Anegón & Herrero-Solana, 1999;Docampo & Bessoule, 2019;Gantman, 2012;King, 2004;May, 1997;Mueller, 2016;Rahman & Fukui, 2003;Rousseau & Rousseau, 1998;Satish, 2021;Vinkler, 2018), and in recent times, e.g. last 50-60 years, all the scientific achievements that have been awarded with Nobel Prizes have come from rich and highly developed countries, with Federico Leloir from Argentina being perhaps the only exception to this general rule.…”
Section: Aim Of This Studymentioning
confidence: 99%
“…However, before drilling down into the details of what makes a research system more or less efficient, the economic factor must also be considered. Many studies have demonstrated that scientific wealth correlates with economic wealth (e.g., Allik et al, 2020;Cimini et al, 2014;Cole & Phelan, 1999;Docampo & Bessoule, 2019;Gantman, 2012;King, 2004;May, 1997;Mueller, 2016;Rahman & Fukui, 2003;Rousseau & Rousseau, 1998), which suggests that countries with medium or low GDP per capita might contribute very little to scientific progress. Such countries may have insufficient economic resources to fund and maintain a competitive research system or to develop the efficient functional structures required to perform research efficiently and compete successfully with richer countries in the advancement of science.…”
Section: Introductionmentioning
confidence: 99%
“…Authorship on these articles credits contributions of individual team members with diverse expertise and skills [17][18][19][20][21], but choosing the best method to evaluate research, for example to identify potential experts, recruits and collaborators, remains a challenge [22]. Presently, the impact of individual contributors [23], journals [24], institutions and nations [25] is predominantly estimated based on citation counts of scientific articles (for reviews see [5,[26][27][28]). In a frequent scenario, a user interested in a specific topic queries a bibliographic database, scrutinizes the resulting list of relevant publications and learns readily about scientific advances.…”
Section: Introductionmentioning
confidence: 99%